MENINGKATKAN KEMAMPUAN MENYUSUN PERANGKAT PEMBELAJARAN DALAM MATA KULIAH PERENCANAAN PEMBELAJARAN MELALUI MODEL KOTIPARE PADA MAHASISWA SEMESTER V JURUSAN PENDIDIKAN BAHASA INGGRIS FKIP- UNIPA SURABAYA - Rahayu, Endang Mastuti (Buana Bastra, 2014)
Abstrak In teaching learning activity, a lecturer does not only convey the material but also should try to make the courses are delivered into a fun learning activities and easily understood by students. If the lecturer can not deliver the material with appropriate and attractive , so that students have difficulty in learning. Actually, the lecturer can use a model of learning by involving more students in the learning process . Learning is a complex process that occurs in all people and last a lifetime since he was a baby up to the adult . One sign that a person has to learn about something, that is a change in her behavior. Changes will occur when the person’s experiencing in real learning process . This means that students can do their own learning activities ( reading, writing, doing assignments, and so on), then the student should gain their experience of learning in real life as well. One of the things that combine the reality with learning activities and students’ experiences is model of Cooperative Think Pair Share (KOTIPARE). The learning model is an important role in the set of learning equipment.. Based on the results of action research, KOTIPARE models improves the students ability in learning aids development. It shows that the increasing of the students ability is 37 % to 67 % on the first cycle , then either the second cycle increased by 22% to 89 %. Key words: Cooperative model of Think Pair Share, learning aids development